Developmental Origins of Transgenerational Sperm Histone Retention Following Ancestral Exposures - Ben Maamar, Millissia (Dev Biol, 2020)
Numerous environmental toxicants have been shown to induce the epigenetic transgenerational inheritance of disease and phenotypic variation. Alterations in the germline epigenome are necessary to transmit transgenerational phenotypes. In previous studies, the pesticide DDT (dichlorodiphenyltrichloroethane) and the agricultural fungicide vinclozolin were shown to promote the transgenerational inheritance of sperm differential DNA methylation regions, non-coding RNAs and histone retention, which are termed epimutations. These epimutations are able to mediate this epigenetic inheritance of disease and phenotypic variation. The current study was designed to investigate the developmental origins of the transgenerational differential histone retention sites (called DHRs) during gametogenesis of the sperm. Vinclozolin and DDT were independently used to promote the epigenetic transgenerational inheritance of these DHRs. Male control lineage, DDT lineage and vinclozolin lineage F3 generation rats were used to isolate round spermatids, caput epididymal spermatozoa, and caudal sperm. The DHRs distinguishing the control versus DDT lineage or vinclozolin lineage samples were determined at these three developmental stages. DHRs and a reproducible core of histone H3 retention sites were observed using an H3 chromatin immunoprecipitation-sequencing (ChIP-Seq) analysis in each of the germ cell populations. The chromosomal locations and genomic features of the DHRs were analyzed. A cascade of epigenetic histone retention site alterations was found to be initiated in the round spermatids and then further modified during epididymal sperm maturation. Observations show that in addition to alterations in sperm DNA methylation and ncRNA expression previously identified, the induction of differential histone retention sites (DHRs) in the later stages of spermatogenesis also occurs. This novel component of epigenetic programming during spermatogenesis can be environmentally altered and transmitted to subsequent generations through epigenetic transgenerational inheritance.